PENGARUH PENAMBAHAN KONSENTRASI NaCl TERHADAP NILAI KELUARAN LISTRIK BIOBATERAI SARI BUAH MENGKUDU - Ety Jumiati; Miftahul Husnah; Riadina Siregar (Universitas Riau, 2023)
Biobattery is a tool that can generate electrical energy from nature that is environmentally friendly, such as noni juice with the addition of NaCl concentration (0%, 10%, 20%). The purpose of this study (i) to determine the pH of the noni juice (ii) for the electrical conductivity of the noni juice (iii) to determine the electrical voltage of the noni juice (iv) to determine the electric current of the noni juice. This study used the galvanic cell method using copper (Cu) and zinc (Zn) electrodes. Based on the results of research conducted on noni juice, the highest value was obtained for noni juice with the addition of 20% NaCl concentration with pH: 2.5, Electrical conductivity: 4915 mS/cm3, voltage: 2.32 V, electric current: 3.12 mA, electric power: 7.23 mW. It can be stated that the lower the pH value, the higher the concentration of NaCl used, the greater the voltage, current, and electrical power obtained. In this study, the ability of noni juice to turn on a white LED light for 2 hours can light up with a stable voltage drop.